Methodological Principles of Poly-Artistic Education of a Person in the Integrated Education System - Omelchenko, Anetta; Grigoryeva, Victoria; Sokolova, Оlgа; Vientseva, Nadezhda (Journal of History Culture and Art Research, 2019)
The article outlines the methodological principles of the artistic education of an individual in the system of integrated artistic education. It is proved that the methodological basis of the integrative processes in education is the philosophical, psychological and cultural conditions and concepts. The determinants of artistic and pedagogical integration necessary for the construction of the integration theory in the field of artistic education and poly-artistic upbringing of the personality are revealed. It is determined that the manifestation of the integration specificity in the field of artistic education is due to the action of psychophysiological mechanisms, and human-centeredness is the fundamental feature of didactic integration. The classification of different categories of integration in pedagogy and didactics is given. The influence of integrative processes on the consciousness and sensory-sensual sphere of a person is considered. It is determined that the psychological preconditions of integrated learning are the peculiarities of human thinking, which organically combines sensual, imaginative-figurative, rational-logical, and creative-intuitive aspects of cognition. The necessity for developing the content of integrated courses and their corresponding technological support is substantiated.